MEMS On/off and x2 Optical Switch with Integrated Fiber Alignment Capability - Cheah, Wei Leow; Mohammad, A .B. (2004)
An on/off free space optical switch is described in this paper. The device consists of intersecting cantilevers and is electrostatically actuated. A fiber is put onto the cantilevers and by controlling the position of the flber through actuation, switching operation can be achieved. The device is also suitable for inpackage fiber alignment application, where the cantilevers can be used as passive or active fiber alignment microstructure.